Genome-wide association study of Fuchs’ endothelial corneal dystrophy in the German population - Juliane Fechner; Guilherme B. Neumann; Fabia Murza; Leonard Matthias; Marcus Walckling; Claudia Brockmann; Thomas A. Fuchsluger; Tobias Brockmann (Human Genetics, 2025)
The genetic etiology of Fuchs Endothelial Corneal Dystrophy (FECD) is not yet fully elucidated. While the disease is widespread and the leading indication for corneal transplantation in the Western world, the concurrent shortage of corneal transplants underscores the urgent need for further research into the underlying mechanisms. Such investigations could enable the development of innovative therapeutic strategies. Therefore, we aimed to verify candidate genes previously identified and sought after novel variants in the German population. Undertaking a genome wide association study (GWAS) using the Axiom™ Precision Medicine Diversity Array on 157 FECD cases and 309 controls, followed by pathway enrichment analysis, we were able to confirm the significance of the TCF4 locus (rs613872, p = 8.0 × 10 − 23 , OR = 8.60, h 2 = 0.72) and identified a range of novel variants. Further fine-mapping highlighted novel candidate SNPs, such as on chromosome 5 in the SEMA6A gene (rs153643, p = 3.1 × 10 − 9 , OR = 2.75, h 2 = 0.30), and on chromosome 19 in the DNAJC19P3 gene (rs62117964, p = 3.3 × 10 − 8 , OR = 3.61, h 2 = 0.29). SEMA6A gene is involved in apoptotic pathways and cytoskeletal remodeling, making it an interesting candidate gene for further investigations as a potential therapeutic target. Furthermore, several variants were identified in lncRNAs, which presumably influence the expression of nearby protein-coding genes. For example, LOC105372130 , which is associated with corneal hysteresis and corneal resistance factor, may influence the expression of TCF4 .